Silicon-carbon negative electrode material and preparation method and application thereof
By using porous carbon to load amorphous silicon particles in the negative electrode material of lithium-ion battery and doping nitrogen, phosphorus and boron elements, the shortcomings of traditional materials in high energy density and high rate performance are solved, and better cycle performance and rate performance are achieved.
Patent Information
- Application Number
- CN202411640793.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Traditional negative electrode graphite materials are difficult to meet the needs of high energy density and high rate performance of lithium-ion batteries. The volume expansion of amorphous silicon materials during the lithium-ion embedding process leads to attenuation of performance and weak conductivity.
A porous carbon support is used to load amorphous silicon particles and coat them with a carbon coating layer on the surface. Nitrogen, phosphorus and boron elements are uniformly doped in the porous carbon to form a silicon carbon negative electrode material.
The cycling performance, mechanical strength and reversible capacity of silicon-carbon anode materials are improved, and the rate performance and service life are enhanced.
Smart Images

Figure CN119153671B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery electrode materials, and in particular to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Traditional negative electrode graphite materials are difficult to meet the current requirements of high energy density and high rate performance of lithium-ion batteries. Amorphous silicon is considered to be the best negative electrode material for the next generation of lithium-ion batteries due to its extremely high mass specific capacity of 4200mAh / g, low lithium insertion potential, abundant reserves and high safety performance. However, the phase change reaction of silicon materials during the lithium ion insertion and extraction process will cause amorphous silicon particles to undergo a dramatic volume expansion (about 300%), which can easily cause amorphous silicon particles to break and pulverize, resulting in the electrode coating and current collector peeling off, which is manifested as rapid capacity decay in performance; at the same time, the conductivity of silicon materials themselves is weak, which inhibits the electrochemical performance. Therefore, silicon materials need to reduce volume expansion, improve cycle performance and enhance conductivity, which is of great significance for their application in lithium-ion batteries.
[0003] Existing approaches to improving the electrochemical performance of silicon materials include nano-sizing the silicon material particles, compounding with other materials to form a certain special structure, or doping the surface with nitrogen, phosphorus, etc. Although these can improve the performance to a certain extent, they still cannot meet the requirements of low expansion, high capacity and long cycle of the material.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide a silicon-carbon negative electrode material which not only has excellent cycle performance and high mechanical strength, but also has high reversible capacity and good rate performance.
[0006] The second object of the present invention is to provide a method for preparing a silicon-carbon negative electrode material, which has a simple process, high efficiency, high success rate and is suitable for factory production.
[0007] The third object of the present invention is to provide an application of a silicon-carbon negative electrode material, which is beneficial to improving the working performance of a lithium-ion secondary battery.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, a silicon-carbon negative electrode material comprises a porous carbon carrier, amorphous silicon particles loaded in the pores of the porous carbon carrier, and a carbon coating layer coated on the surface of the porous carbon carrier;
[0010] The porous carbon carrier contains nitrogen, phosphorus and boron elements;
[0011] Among them, the total content of nitrogen, phosphorus and boron in the silicon-carbon negative electrode material does not exceed 5wt%.
[0012] Furthermore, the content of the nitrogen element in the silicon-carbon negative electrode material is 1wt%~3wt%;
[0013] Preferably, the content of phosphorus in the silicon-carbon negative electrode material does not exceed 2wt%;
[0014] Preferably, the content of the boron element in the silicon-carbon negative electrode material does not exceed 2 wt %.
[0015] Furthermore, the specific surface area of the silicon-carbon negative electrode material is 1m² / g~10m² / g;
[0016] Preferably, the median particle size D50 of the silicon-carbon negative electrode material is 2 μm to 15 μm;
[0017] Preferably, the tap density of the silicon-carbon negative electrode material is 0.8 g / cm 3 ~1.5g / cm 3 .
[0018] Furthermore, the amorphous silicon particles account for 10wt% to 90wt%;
[0019] Preferably, the size of the amorphous silicon particles is 0.5 nm to 80 nm;
[0020] Preferably, among the amorphous silicon particles, particles with a size of 0.5 nm to 40 nm account for 45wt% to 55wt%, particles with a size of 41 nm to 60 nm account for 25wt% to 35wt%, and particles with a size of 61 nm to 80 nm account for 10wt% to 20wt%.
[0021] Furthermore, the thickness of the carbon coating layer is 5nm~20nm.
[0022] In a second aspect, a method for preparing the silicon-carbon negative electrode material described in any one of the above items comprises the following steps:
[0023] (a) mixing a nitrogen-rich carbon source, a phosphorus source and a boron source, then performing a carbonization treatment, and then performing an activation treatment to obtain a porous carbon carrier containing nitrogen, phosphorus and boron elements;
[0024] (b) thermally decomposing a silane compound and depositing it in the pores of the porous carbon carrier to obtain a silicon-carbon precursor, and subjecting the silicon-carbon precursor to an organic carbon source coating treatment to obtain the silicon-carbon negative electrode material.
[0025] Furthermore, the total content of nitrogen, phosphorus and boron in the porous carbon carrier is 2wt% to 10wt%;
[0026] Preferably, the nitrogen content in the porous carbon carrier is 2wt%~5wt%;
[0027] Preferably, the phosphorus content in the porous carbon carrier does not exceed 3wt%;
[0028] Preferably, the boron content in the porous carbon carrier does not exceed 2wt%;
[0029] Preferably, the specific surface area of the porous carbon support is 800 m² / g to 2500 m² / g;
[0030] Preferably, the pore volume of the porous carbon carrier is 0.5 cm³ / g~1.5 cm³ / g.
[0031] Further, the nitrogen-rich carbon source includes at least one of bovine serum albumin, soy protein, peanut protein, rice protein, egg white protein and milk protein;
[0032] Preferably, the phosphorus source includes at least one of diphenylphosphine, triphenylphosphine, diphenyl phosphate and tetraphenylphosphonium bromide;
[0033] Preferably, the boron source includes at least one of boric acid, borax, ammonium borate, phenylboric acid, p-formylphenylboric acid and boron triiodide.
[0034] Furthermore, the temperature of the carbonization treatment is 700°C to 1300°C, and the holding time of the carbonization treatment is 0.5h to 8h;
[0035] Preferably, the activation treatment includes at least one of steam activation treatment, air activation treatment and carbon dioxide activation treatment;
[0036] Preferably, the temperature of the activation treatment is 500° C. to 1000° C., and the time of the activation treatment is 6 h to 30 h.
[0037] A third aspect is an application of the silicon-carbon negative electrode material described in any one of the above items in a lithium-ion secondary battery.
[0038] Compared with the prior art, the present invention has at least the following beneficial effects:
[0039] The silicon-carbon negative electrode material provided by the present invention is uniformly doped with nitrogen, phosphorus and boron in situ on the carbon substrate porous carbon. Compared with undoped or element-doped porous carbon on the surface of particles, this invention improves the various performances of the silicon-carbon negative electrode material from the structure and performance of the porous carbon substrate; nitrogen uniform doping better improves the degree of graphitization of the porous carbon, so that the porous carbon obtains high conductivity; phosphorus causes carbon lattice distortion in the carbon material and enhances the mechanical strength of the porous carbon; at the same time, nitrogen and phosphorus react in the process of preparing porous carbon to form a skeleton structure with a buffering effect, which can further offset the stress generated by the volume expansion of the lithium battery during the charging and discharging process, thereby improving the service life of the material; porous carbon is doped with pre-buried boron, on the one hand, boron itself has high structural stability, on the other hand, boron has a high ability to insert and remove lithium ions, which can enhance the capacity of the silicon-carbon negative electrode material. Therefore, the lithium battery prepared by the silicon-carbon negative electrode material of the present invention not only improves the reversible capacity, but also prolongs the service life, and also has better rate performance.
[0040] The method for preparing the silicon-carbon negative electrode material provided by the present invention has simple process, high efficiency, high success rate and is suitable for factory production.
[0041] The application of the silicon-carbon negative electrode material provided by the present invention is beneficial to improving the working performance of lithium-ion secondary batteries and can achieve outstanding application effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0043] Figure 1 This is a SEM image of the porous carbon support obtained in Experimental Example 1 of the present invention;
[0044] Figure 2 This is the first charge and discharge curve of the lithium button cell using the silicon-carbon negative electrode material obtained in Experimental Example 2 of the present invention. DETAILED DESCRIPTION
[0045] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] According to a first aspect of the present invention, there is provided a silicon-carbon negative electrode material, comprising a porous carbon carrier, amorphous silicon particles loaded in the pores of the porous carbon carrier, and a carbon coating layer coated on the surface of the porous carbon carrier;
[0047] The porous carbon support contains nitrogen, phosphorus and boron elements;
[0048] The total content of nitrogen, phosphorus and boron in the silicon-carbon negative electrode material does not exceed 5wt%.
[0049] In the present invention, nitrogen is evenly distributed in the porous carbon, which can increase the degree of graphitization of the porous carbon, reduce the impedance of the silicon-carbon negative electrode material, and increase the electronic conductivity, thereby improving the power performance; boron can additionally increase the lithium storage capacity of the material, thereby improving the reversible capacity; phosphorus can distort the carbon lattice, further adjust the structure of the porous carbon, and make it have higher compressive resistance.
[0050] In summary, in the silicon-carbon negative electrode material provided by the present invention, the nitrogen element can make the porous carbon obtain a higher degree of graphitization, thereby improving the electronic conductivity of the material; the boron element can reversibly react with lithium ions in the battery to generate Li5B, thereby providing additional reversible capacity; the phosphorus element can distort the carbon lattice in the material and further adjust the structure of the carbon material, thereby giving the porous carbon material higher mechanical strength and stronger compressive resistance.
[0051] Therefore, the silicon-carbon negative electrode material of the present invention has more lithium ion storage active sites to improve the reversible capacity, has higher electronic conductivity to obtain better rate performance, and has stronger mechanical strength to better alleviate lithium insertion expansion.
[0052] In a preferred embodiment, the content of nitrogen in the silicon-carbon negative electrode material can be 1wt%~3wt%, which can fully improve the graphitization degree of porous carbon, effectively reduce the material impedance, and improve the electronic conductivity, so as to be more conducive to improving the power performance of the material; the content of phosphorus in the silicon-carbon negative electrode material does not exceed 2wt%, which can cause the carbon lattice to distort and further adjust the porous carbon structure, which is more conducive to enhancing the mechanical strength of the material and improving the material's compressive strength; the content of boron in the silicon-carbon negative electrode material does not exceed 2wt%, which is more conducive to additionally increasing the lithium storage capacity, so as to fully improve the reversible capacity of the material. Element doping is limited by cost and preparation conditions, especially element doping in carbon substrates. The amount of element doping is affected by carbonization temperature and pore-forming method, and the final doping amount is difficult to reach a high level; on the current basis, the performance of the silicon-carbon negative electrode material of the present invention has been greatly improved.
[0053] The silicon-carbon negative electrode material of the present invention can take into account better cycle performance, higher reversible capacity and better rate performance, and at the same time has high mechanical strength and effectively alleviates lithium insertion expansion.
[0054] In a preferred embodiment, the specific surface area of the silicon-carbon negative electrode material can be 1m² / g~10m² / g, and its typical but non-limiting specific surface area is, for example, 1m² / g, 2m² / g, 3m² / g, 4m² / g, 5m² / g, 6m² / g, 7m² / g, 8m² / g, 9m² / g, 10m² / g, and can be further preferably 2m² / g~8m² / g, and further preferably 2m² / g~5m² / g.
[0055] In a preferred embodiment, the median particle size D50 of the silicon-carbon negative electrode material can be 2μm~15μm, and its typical but non-limiting median particle size D50 is, for example, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, and can be further preferably 4μm~10μm, and further preferably 4μm~6μm.
[0056] In a preferred embodiment, the tap density of the silicon-carbon negative electrode material can be 0.8 g / cm 3 ~1.5g / cm 3 , with a typical but non-limiting tap density of, for example, 0.8 g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , which may be further preferably 0.9 g / cm 3 ~1.2g / cm 3 .
[0057] In a preferred embodiment, the proportion of amorphous silicon particles in the silicon-carbon negative electrode material can be 10wt%~90wt%, and its typical but non-limiting proportions are, for example, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, and 90wt%, and can be further preferably 40wt%~70wt%, and further preferably 40wt%~60wt%.
[0058] In a preferred embodiment, the size of the amorphous silicon particles can be 0.5nm~80nm; wherein the proportion of particles with a size of 0.5nm~40nm in the amorphous silicon particles can be 45wt%~55wt%, for example, 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, but not limited thereto; the proportion of particles with a size of 41nm~60nm in the amorphous silicon particles can be 25wt%~35wt%, for example For example, it can be 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, and 35wt%, but is not limited to this; the proportion of particles with a size of 61nm~80nm in the amorphous silicon particles can be 10wt%~20wt%, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, and 20wt%, but is not limited to this.
[0059] In a preferred embodiment, the thickness of the carbon coating layer can be 5 nm to 20 nm, and its typical but non-limiting thickness is, for example, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, and 20 nm.
[0060] According to a second aspect of the present invention, there is provided a method for preparing the silicon-carbon negative electrode material as described in any one of the above, comprising the following steps:
[0061] (a) mixing a nitrogen-rich carbon source, a phosphorus source and a boron source, then performing a carbonization treatment, and then performing an activation treatment to obtain a porous carbon carrier containing nitrogen, phosphorus and boron elements;
[0062] (b) thermally decomposing the silane compound and depositing it in the pores of the porous carbon support obtained in step (a) to obtain a silicon-carbon precursor, and coating the silicon-carbon precursor with an organic carbon source to obtain a silicon-carbon negative electrode material.
[0063] The method for preparing the silicon-carbon negative electrode material provided by the present invention has simple process, high efficiency, high success rate and is suitable for factory production.
[0064] In a preferred embodiment, the total content of nitrogen, phosphorus and boron in the porous carbon carrier can be 2wt%~10wt%, and its typical but non-limiting content is, for example, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, and can be further preferably 4wt%~9wt%.
[0065] In a preferred embodiment, the nitrogen content in the porous carbon carrier can be 2wt%~5wt%, which is more conducive to making the porous carbon obtain a higher degree of graphitization and improving the electronic conductivity.
[0066] In a preferred embodiment, the phosphorus content in the porous carbon carrier does not exceed 3wt%, which is more conducive to making the porous carbon material have higher mechanical strength and stronger compressive resistance.
[0067] In a preferred embodiment, the boron content in the porous carbon carrier does not exceed 2 wt %, which is more conducive to improving the reversible capacity.
[0068] In a preferred embodiment, the specific surface area of the porous carbon carrier can be 800m² / g~2500m² / g, and its typical but non-limiting specific surface area is, for example, 800m² / g, 900m² / g, 1000m² / g, 1200m² / g, 1500m² / g, 2000m² / g, 2500m² / g, and can be further preferably 1000m² / g~2000m² / g, and further preferably 1200m² / g~1800m² / g.
[0069] In a preferred embodiment, the pore volume of the porous carbon carrier can be 0.5cm³ / g~1.5cm³ / g, and its typical but non-limiting pore volume is, for example, 0.5cm³ / g, 0.6cm³ / g, 0.7cm³ / g, 0.8cm³ / g, 0.9cm³ / g, 1.0cm³ / g, 1.1cm³ / g, 1.2cm³ / g, 1.3cm³ / g, 1.4cm³ / g, 1.5cm³ / g, and can be further preferably 0.7cm³ / g~1.2cm³ / g, and further preferably 0.8cm³ / g~1.2cm³ / g.
[0070] In the present invention, based on the uniform distribution of nitrogen in the nitrogen-rich carbon source material itself, a phosphorus source and a boron source are added to prepare in situ a porous carbon carrier with uniform distribution of nitrogen, phosphorus and boron elements.
[0071] In a preferred embodiment, the nitrogen-rich carbon source includes but is not limited to at least one of bovine serum albumin, soy protein, peanut protein, rice protein, egg white protein and milk protein; the phosphorus source includes but is not limited to at least one of diphenylphosphine, triphenylphosphine, diphenyl phosphate and tetraphenylphosphonium bromide; the boron source includes but is not limited to at least one of boric acid, borax, ammonium borate, phenylboric acid, paraformylphenylboric acid and boron triiodide.
[0072] In the present invention, a nitrogen-rich carbon source, a phosphorus source and a boron source are mixed and dissolved in a solvent, fully mixed and then dried to obtain a carbon precursor, and then the carbon precursor is subjected to a one-step high-temperature fluidized carbonization treatment to obtain a carbide, and then the carbide is crushed and activated to obtain a porous carbon carrier with uniform distribution of nitrogen, phosphorus and boron elements;
[0073] Wherein, the solvent includes but is not limited to at least one of pure water, ethanol, ether and acetone;
[0074] The drying method can be at least one of natural air drying, heating and stirring drying, microwave drying and spray drying.
[0075] In a preferred embodiment, the temperature of the high-temperature fluidized carbonization treatment can be 700°C to 1300°C, and typical but non-limiting temperatures are, for example, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, and 1300°C; the holding time of the carbonization treatment can be 0.5h to 8h, and typical but non-limiting times are, for example, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, and 8h. The doping elements in the carbon material are lost during the high-temperature carbonization. In order to ensure that the doping element content is at a high level and the carbonization degree is high, 1100°C is preferably used as the ideal carbonization temperature.
[0076] In a preferred embodiment, the activation treatment includes but is not limited to at least one of steam activation treatment, air activation treatment and carbon dioxide activation treatment;
[0077] The temperature of the activation treatment can be 500°C~1000°C, and typical but non-limiting temperatures are 500°C, 600°C, 700°C, 800°C, 900°C, and 1000°C; the time of the activation treatment can be 6h~30h, and typical but non-limiting times are 6h, 8h, 10h, 15h, 20h, 25h, and 30h.
[0078] In the present invention, the silane compound is adsorbed in the porous carbon pores and decomposes to generate nano-amorphous silicon particles, and the amorphous silicon particles are deposited in the porous carbon pores, thereby obtaining a silicon-carbon precursor;
[0079] The silane compound includes but is not limited to at least one of monosilane, disilane, tetrafluorosilane and trichlorosilane;
[0080] The amorphous silicon particle deposition method includes but is not limited to chemical vapor deposition. The temperature of chemical vapor deposition can be 400° C. to 900° C., and its typical but non-limiting temperature is, for example, 400° C., 500° C., 600° C., 700° C., 800° C., and 900° C. The time of chemical vapor deposition can be 1 hour to 20 hours, and its typical but non-limiting time is, for example, 1 hour, 4 hours, 8 hours, 12 hours, 16 hours, and 20 hours.
[0081] Chemical vapor deposition may be performed in an inert atmosphere, which includes but is not limited to at least one of nitrogen, argon and helium.
[0082] In the present invention, the organic carbon source is pyrolyzed and coated on the surface of the silicon-carbon precursor, which can not only form a protective layer but also further reduce the specific surface area of the silicon-carbon negative electrode material;
[0083] Wherein, the organic carbon source includes but is not limited to at least one of methane, acetylene, propane and propylene;
[0084] The organic carbon source coating method includes but is not limited to chemical vapor deposition. The temperature of chemical vapor deposition can be 550°C~950°C, and its typical but non-limiting temperatures are, for example, 550°C, 650°C, 750°C, 850°C, and 950°C. The time of chemical vapor deposition can be 1h-20h, and its typical but non-limiting time is, for example, 1h, 4h, 8h, 12h, 16h, and 20h.
[0085] In summary, the preparation method of the silicon-carbon negative electrode material provided by the present invention is to first prepare a porous carbon carrier in which nitrogen, phosphorus and boron are evenly distributed; then, a silane compound is thermally decomposed and deposited in the pores of the porous carbon carrier to obtain a silicon-carbon precursor; and then, the silicon-carbon precursor is coated with an organic carbon source to obtain a silicon-carbon negative electrode material.
[0086] According to a third aspect of the present invention, there is provided a use of the silicon-carbon negative electrode material described in any one of the above items in a lithium-ion secondary battery.
[0087] The application of the silicon-carbon negative electrode material provided by the present invention exhibits high reversible capacity, high rate performance and high compressive strength in lithium-ion secondary batteries, which is beneficial to improving the working performance of lithium-ion secondary batteries and can achieve outstanding application effects.
[0088] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0089] Example 1
[0090] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0091] S1: Soy protein, triphenylphosphine and boric acid are mixed and dissolved in ether in a mass ratio of 8:1.2:0.8, mixed evenly and then spray-dried to obtain a granular carbon precursor;
[0092] Under the protection of inert gas (nitrogen), the carbon precursor is carbonized at a high temperature of 1100°C for 3 hours to obtain a carbide, which is then pulverized and subjected to a water vapor activation pore forming treatment at an activation temperature of 900°C for 25 hours to obtain a porous carbon carrier in which nitrogen, phosphorus and boron are uniformly distributed.
[0093] S2: At 450° C., a mixed gas of monosilane and nitrogen was introduced into a reactor containing the porous carbon support for 5.5 h, and then the temperature was reduced to 350° C. for 4 h to obtain a silicon-carbon precursor;
[0094] S3: Continuing with step S2, the temperature was raised to 600°C, a mixed gas of acetylene and nitrogen was introduced, and the temperature was kept at this temperature for 6 hours, and then the temperature was lowered to below 100°C, and air passivated to obtain a silicon-carbon negative electrode material.
[0095] Example 2
[0096] This embodiment provides a method for preparing a silicon-carbon negative electrode material, which is different from Embodiment 1 only in that, in step S1, the mass ratio of soybean protein, triphenylphosphine and boric acid is 6.5:2:1.5;
[0097] The remaining steps and process parameters are the same as those in Example 1 to obtain a porous carbon carrier and a silicon-carbon negative electrode material.
[0098] Example 3
[0099] This embodiment provides a method for preparing a silicon-carbon negative electrode material, which is different from Embodiment 1 only in that, in step S1, the mass ratio of soybean protein, triphenylphosphine and boric acid is 6.5:1.5:2;
[0100] The remaining steps and process parameters are the same as those in Example 1 to obtain a porous carbon carrier and a silicon-carbon negative electrode material.
[0101] Example 4
[0102] This embodiment provides a method for preparing a silicon-carbon negative electrode material, which is different from Embodiment 1 only in that, in step S2, the mixed gas of monosilane and nitrogen is introduced into the reactor and kept warm for 6.5 hours;
[0103] The remaining steps and process parameters are the same as those in Example 1 to obtain a silicon-carbon negative electrode material.
[0104] Example 5
[0105] This embodiment provides a method for preparing a silicon-carbon negative electrode material, which is different from Embodiment 1 only in that, in step S2, a mixed gas of monosilane and nitrogen is introduced into a reactor at 500° C.;
[0106] The remaining steps and process parameters are the same as those in Example 1 to obtain a silicon-carbon negative electrode material.
[0107] Example 6
[0108] This embodiment provides a method for preparing a silicon-carbon negative electrode material, which is different from Embodiment 1 only in that, in step S3, the temperature holding time of the mixed gas of acetylene and nitrogen is 8 hours;
[0109] The remaining steps and process parameters are the same as those in Example 1 to obtain a silicon-carbon negative electrode material.
[0110] Example 7
[0111] This embodiment provides a method for preparing a silicon-carbon negative electrode material, which is different from Embodiment 1 only in that, in step S1, an equal amount of bovine serum albumin is used to replace soybean protein;
[0112] The remaining steps and process parameters are the same as those in Example 1 to obtain a porous carbon carrier and a silicon-carbon negative electrode material.
[0113] Example 8
[0114] This embodiment provides a method for preparing a silicon-carbon negative electrode material, which is different from Embodiment 1 only in that, in step S1, an equal amount of peanut protein is used to replace soybean protein;
[0115] The remaining steps and process parameters are the same as those in Example 1 to obtain a porous carbon carrier and a silicon-carbon negative electrode material.
[0116] Example 9
[0117] This embodiment provides a method for preparing a silicon-carbon negative electrode material, which is different from Embodiment 1 only in that, in step S1, an equal amount of diphenylphosphine is used to replace triphenylphosphine;
[0118] The remaining steps and process parameters are the same as those in Example 1 to obtain a porous carbon carrier and a silicon-carbon negative electrode material.
[0119] Example 10
[0120] This embodiment provides a method for preparing a silicon-carbon negative electrode material, which is different from Embodiment 1 only in that, in step S1, an equal amount of diphenyl phosphate is used to replace triphenyl phosphine;
[0121] The remaining steps and process parameters are the same as those in Example 1 to obtain a porous carbon carrier and a silicon-carbon negative electrode material.
[0122] Embodiment 11
[0123] This embodiment provides a method for preparing a silicon-carbon negative electrode material, which is different from Embodiment 1 only in that, in step S1, an equal amount of ammonium borate is used to replace boric acid;
[0124] The remaining steps and process parameters are the same as those in Example 1 to obtain a porous carbon carrier and a silicon-carbon negative electrode material.
[0125] Example 12
[0126] This embodiment provides a method for preparing a silicon-carbon negative electrode material, which is different from Embodiment 1 only in that, in step S1, an equal amount of phenylboric acid is used to replace boric acid;
[0127] The remaining steps and process parameters are the same as those in Example 1 to obtain a porous carbon carrier and a silicon-carbon negative electrode material.
[0128] Comparative Example 1
[0129] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0130] S1: Soy protein and boric acid are mixed and dissolved in ether in a mass ratio of 9.2:0.8, mixed evenly and then spray-dried to obtain a granular carbon precursor;
[0131] Under the protection of inert gas (nitrogen), the carbon precursor was carbonized at a high temperature of 1100°C for 3 hours to obtain a carbide, and the carbide was subjected to a water vapor activation pore forming treatment after being crushed, at an activation temperature of 900°C and an activation time of 25 hours to obtain a porous carbon carrier;
[0132] S2: At 450° C., a mixed gas of monosilane and nitrogen was introduced into a reactor containing the porous carbon support for 5.5 h, and then the temperature was reduced to 350° C. for 4 h to obtain a silicon-carbon precursor;
[0133] S3: Continuing with step S2, the temperature was raised to 600°C, a mixed gas of acetylene and nitrogen was introduced, and the temperature was kept at this temperature for 6 hours, and then the temperature was lowered to below 100°C, and air passivated to obtain a silicon-carbon negative electrode material.
[0134] Comparative Example 2
[0135] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0136] S1: Soy protein and triphenylphosphine are mixed and dissolved in ether in a mass ratio of 9.2:0.8, mixed evenly and then spray-dried to obtain a granular carbon precursor;
[0137] Under the protection of inert gas (nitrogen), the carbon precursor was carbonized at a high temperature of 1100°C for 3 hours to obtain a carbide, and the carbide was subjected to a water vapor activation pore forming treatment after being crushed, at an activation temperature of 900°C and an activation time of 25 hours to obtain a porous carbon carrier;
[0138] S2: At 450° C., a mixed gas of monosilane and nitrogen was introduced into a reactor containing the porous carbon support for 5.5 h, and then the temperature was reduced to 350° C. for 4 h to obtain a silicon-carbon precursor;
[0139] S3: Continuing with step S2, the temperature was raised to 600°C, a mixed gas of acetylene and nitrogen was introduced, and the temperature was kept at this temperature for 6 hours, and then the temperature was lowered to below 100°C, and air passivated to obtain a silicon-carbon negative electrode material.
[0140] Comparative Example 3
[0141] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0142] S1: dissolving soybean protein in ether and spray drying to obtain a granular carbon precursor;
[0143] Under the protection of inert gas (nitrogen), the carbon precursor was carbonized at a high temperature of 1100°C for 3 hours to obtain a carbide, and the carbide was subjected to a water vapor activation pore forming treatment after being crushed, at an activation temperature of 900°C and an activation time of 25 hours to obtain a porous carbon carrier;
[0144] S2: At 450° C., a mixed gas of monosilane and nitrogen was introduced into a reactor containing the porous carbon support for 5.5 h, and then the temperature was reduced to 350° C. for 4 h to obtain a silicon-carbon precursor;
[0145] S3: Continuing with step S2, the temperature was raised to 600°C, a mixed gas of acetylene and nitrogen was introduced, and the temperature was kept at this temperature for 6 hours, and then the temperature was lowered to below 100°C, and air passivated to obtain a silicon-carbon negative electrode material.
[0146] Test Example 1
[0147] The content of non-metallic elements was analyzed by German SPECTRO ICP-OES plasma emission spectrometer GREEN. The specific surface area (m² / g) of the material was tested by JW-DX dynamic adsorption specific surface area meter. The morphology and graphic processing of the material were analyzed by field emission scanning electron microscope (SEM) (JSM-7800F).
[0148] The contents of nitrogen, phosphorus and boron in the porous carbon supports obtained in the examples and comparative examples are shown in Table 1.
[0149] The SEM image of the porous carbon support obtained in Example 1 is shown in Figure 1 .
[0150] Table 1
[0151]
[0152] It can be seen from Table 1 that the porous carbon carrier obtained in the embodiment of the present invention has nitrogen, phosphorus and boron evenly distributed in it; at the same time, the content of nitrogen, phosphorus and boron in the porous carbon carrier can be simply achieved by adjusting the ratio of raw materials.
[0153] The contents of nitrogen, phosphorus, boron and silicon in the silicon-carbon negative electrode materials obtained in the examples and comparative examples, as well as the material specific surface area, amorphous silicon particle size and carbon coating layer thickness are shown in Table 2.
[0154] Table 2
[0155]
[0156] Test Example 2
[0157] Button cell battery test:
[0158] The first reversible capacity and first efficiency of the silicon-carbon negative electrode materials obtained in the examples and comparative examples were tested as follows:
[0159] The silicon-carbon negative electrode material, the conductive agent and the binder are mixed in pure water at a mass ratio of 95:1.5:3.5 for homogenization, the solid content is controlled at 48wt%, coated on the copper foil current collector, vacuum baked at 100°C-110°C for 8h, pressed and formed, and then punched to prepare the negative electrode sheet;
[0160] The button half-cell was assembled in a glove box filled with argon. The counter electrode was a metal lithium sheet, the separator used was PE, and the electrolyte was 1 mol / L LiPF6 EC / DMC (Vol 1:1).
[0161] The button cell was charged and discharged. The test process was 0.2C DC to 0V, 0.05C DC to 0V, 0V CV50μA, 0.01C DC to 0V, 0V CV 20μA, Rest 10min, 0.2C CC to 2V.
[0162] The first reversible capacity and efficiency of the silicon-carbon negative electrode materials obtained in the examples and comparative examples were measured, wherein the button cell testing equipment was the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.
[0163] The silicon-carbon negative electrode material powder is mixed with the graphite negative electrode (mass ratio is 10~80:20~90) to obtain a mixed negative electrode powder; the negative electrode powder, Super p, and BP-7 are mixed in pure water at a mass ratio of 92:4:4, the solid content is controlled at 48%, and the slurry is coated on a current collector with a copper foil as the substrate, and placed in a vacuum baking oven at 80℃~100℃ for vacuum baking for 4h~8h; the pole piece is cold pressed using a commercial roller pressing equipment from Kejing, and the pole piece is sliced into small discs with a diameter of 15mm~22mm using a commercial slicing equipment from Kejing to prepare a silicon composite negative electrode pole piece.
[0164] Commercial 523 positive electrode material, SP, and PVDF (polyvinylidene fluoride) were mixed into an appropriate amount of NMP (N-methylpyrrolidone) solvent in a mass ratio of 90:7:3, and the solid content was controlled to be 55%. The mixed slurry was coated on a current collector with an aluminum foil as the substrate, and placed in a vacuum baking oven at 90℃~120℃ for vacuum baking for 4h~8h; the pole pieces were cold pressed using Kejing commercial roller pressing equipment, and the pole pieces were sliced into small discs with a diameter of 15mm~22mm using Kejing commercial slicing equipment to prepare positive electrode pieces; dried at 85℃ under vacuum (-0.1MPa) conditions for 8h, weighed, and the weight of the active substance was calculated.
[0165] The separator used was PE, and the electrolyte was 1 mol / L LiPF6 EC / DMC (Vol 1:1). The CR2430 button-type full battery was assembled in a glove box, and the button-type full battery was left at room temperature for 2h~6h, and activated by charging and discharging at 0.1C on a blue power test system, and then charged and discharged at 1C (voltage range 3.0V~4.2V) for 20~300 cycles.
[0166] The capacity retention rate of the material = the discharge capacity of the last cycle / the discharge capacity of the first cycle × 100%.
[0167] The above test results are shown in Table 3. The first charge and discharge curves of the lithium button cell made of silicon-carbon negative electrode material obtained in Example 1 are shown in Figure 2 Table 3
[0168]
[0169] By comparing the electrochemical performance data of the materials obtained in Example 1 and Comparative Examples 1-3, it can be seen that the porous carbon carrier contains uniformly distributed nitrogen, phosphorus and boron elements, which has a significant improvement effect on the reversible specific capacity, first coulombic efficiency and capacity retention rate of the material; in particular, the reversible specific capacity of the material obtained in Example 1 reaches 2084mAh / g, the first coulombic efficiency at 1.5V reaches 94.0%, the capacity retention rate after 100 cycles reaches 99%, the 1C charging specific capacity reaches 2014mAh / g, and the 1C charging specific capacity retention rate after 50 cycles reaches 93%.
[0170] By comparing the electrochemical performance data of the materials obtained in Example 1 and Example 4-5, it can be seen that the larger the size of the amorphous silicon particles, the more significantly the reversible specific capacity, the first coulombic efficiency and the capacity retention rate will be reduced. The reason is that the larger the particle size of the amorphous silicon, the greater the stress generated during the lithium insertion and delithiation process, which will cause the particles to break and form a larger SEI film, resulting in more consumption of active lithium.
[0171] By comparing the electrochemical performance data of the materials obtained in Example 1 and Example 6, it can be seen that the carbon coating layer of the material obtained in Example 6 is thicker, resulting in a lower capacity retention rate after 100 cycles than that of the material in Example 1, proving that an appropriate thickness of the carbon coating layer is more conducive to improving the cycle performance.
[0172] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A silicon-carbon negative electrode material, characterized in that: The method comprises a porous carbon carrier, amorphous silicon particles loaded in the pores of the porous carbon carrier, and a carbon coating layer coated on the surface of the porous carbon carrier; The porous carbon carrier contains nitrogen, phosphorus and boron elements; Among them, the content of the nitrogen element in the silicon-carbon negative electrode material is 2.05wt%, the content of the phosphorus element in the silicon-carbon negative electrode material is 1.11wt%, and the content of the boron element in the silicon-carbon negative electrode material is 0.91wt%.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The specific surface area of the silicon-carbon negative electrode material is 1m² / g~10m² / g; The median particle size D50 of the silicon-carbon negative electrode material is 2 μm to 15 μm; The tap density of the silicon-carbon negative electrode material is 0.8 g / cm 3 ~1.5g / cm 3 .
3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The amorphous silicon particles account for 10wt% to 90wt%; The size of the amorphous silicon particles is 0.5nm~80nm; Among the amorphous silicon particles, particles with a size of 0.5 nm to 40 nm account for 45 wt% to 55 wt%, particles with a size of 41 nm to 60 nm account for 25 wt% to 35 wt%, and particles with a size of 61 nm to 80 nm account for 10 wt% to 20 wt%.
4. The silicon-carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The thickness of the carbon coating layer is 5nm~20nm.
5. A method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (a) mixing a nitrogen-rich carbon source, a phosphorus source and a boron source, then performing a carbonization treatment, and then performing an activation treatment to obtain a porous carbon carrier containing nitrogen, phosphorus and boron elements; (b) thermally decomposing a silane compound and depositing it in the pores of the porous carbon carrier to obtain a silicon-carbon precursor, and subjecting the silicon-carbon precursor to an organic carbon source coating treatment to obtain the silicon-carbon negative electrode material.
6. The preparation method according to claim 5, characterized in that: The specific surface area of the porous carbon carrier is 800m² / g~2500m² / g; The pore volume of the porous carbon carrier is 0.5 cm³ / g~1.5 cm³ / g.
7. The preparation method according to claim 5, characterized in that: The nitrogen-rich carbon source comprises at least one of bovine serum albumin, soy protein, peanut protein, rice protein, egg white protein and milk protein; The phosphorus source includes at least one of diphenylphosphine, triphenylphosphine, diphenyl phosphate and tetraphenylphosphonium bromide; The boron source includes at least one of boric acid, borax, ammonium borate, phenylboric acid, p-formylphenylboric acid and boron triiodide.
8. The preparation method according to claim 5, characterized in that: The temperature of the carbonization treatment is 700°C to 1300°C, and the holding time of the carbonization treatment is 0.5h to 8h; The activation treatment includes at least one of steam activation treatment, air activation treatment and carbon dioxide activation treatment; The temperature of the activation treatment is 500° C. to 1000° C., and the time of the activation treatment is 6 h to 30 h.
9. Use of the silicon-carbon negative electrode material according to any one of claims 1 to 4 in a lithium-ion secondary battery.
Citation Information
Patent Citations
Porous phosphor-nitrogen-codoped carbon material and preparation method thereof
CN104003368A
Preparation method of heteroatom doped porous carbon material
CN106115653A
Boron-nitrogen-phosphorus ternary doped metal-free carbon material as well as preparation method and application thereof
CN111613801A
Negative electrode material, preparation method thereof and battery
CN118231635A